För naturens bästa - Svensson, Pia (2004)
Nature's Best is a quality-label for Swedish Eco-tourism. It is one of very few active ecotourism labels and the only one that claims quality as its main focus. The objective of this thesis is to evaluate the certification scheme Nature's Best with regards to the values the certification creates for the companies that certify their products. A secondary objective is to evaluate whether Nature's Best is constructed as a quality- or environmental label. The analysis is based on theory concerning service quality, labelling and marketing. The thesis also includes a short description of the eco-tourism market and competing labelling schemes.